(untitled) (Global Journal of Computer Science and Technology, 2019)
Algorithm design plays a significant role in development of any application that is concerned with engineering and technology Advancement in implementation levels of algorithms made a good impact with the model developed Meanwhile the time and space complexity of the execution of the algorithm varies with regard to the input to the algorithm upon fixation of various parametric levels This paper summarizes a survey on various algorithm design techniques and its applications The applicability of the algorithms varies with regard to the problem and the nature of computation levels